2019
DOI: 10.1089/cyber.2019.0121
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Training to Reduce Automatic Action Tendencies Toward Alcohol Using the Virtual Alcohol Approach-Avoidance Task in Heavy Social Drinkers

Abstract: This study aimed to reduce the approach tendency toward alcohol among heavy social drinkers using the Virtual Alcohol Approach-Avoidance Training Task training. A total of 28 heavy social drinkers were randomly assigned to either the training group (n = 14) or the control group (n = 14). The training group was implicitly trained to avoid situations that involved drinking alcohol and to approach situations that involved drinking nonalcoholic beverages. On the other hand, the control group received a sham traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Therefore, a systematic quality appraisal with standardized clinical frameworks or meta-analysis of data was not possible [73,74]. Another issue is that we excluded two papers from the review because it was unclear whether HMDs were used, because of a lack of detailed methodological reporting [75,76]. These methodological shortcomings need to be addressed to further the VR field and bring VR technology to clinical care for patients with ADs.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Therefore, a systematic quality appraisal with standardized clinical frameworks or meta-analysis of data was not possible [73,74]. Another issue is that we excluded two papers from the review because it was unclear whether HMDs were used, because of a lack of detailed methodological reporting [75,76]. These methodological shortcomings need to be addressed to further the VR field and bring VR technology to clinical care for patients with ADs.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The number of studies taken into consideration for each transdiagnostic factor varied. Avoidance was the most studied transdiagnostic factor found in 23 articles (63.89%) ( n = 19 experimental studies and n = 4 case studies) [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], followed by emotion regulation, which was found in eight articles (22.22%; n = 7 experimental studies and n = 1 case study) [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]; aggression, which was found in three experimental studies (8.33%) [ 70 , 71 , 72 ]; impulsivity, which was found in two studies (5.56%; n =1 experimental study and n = 1 case study) [ 71 , 73 ]; and cognitive reappraisal, which was found in two studies (5.56%; n = 1 experimental study and n = 1 case study) [ 63 , 74 ]. No studies were found for the transdiagnostic factor of disinhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding comparisons between VRET and in-vivo exposure, VRET was more effective than the latter in reducing social avoidance in SAD patients and more practical according to therapists in one study [40], but less effective in another [46]. Finally, fewer but promising results were found for the ability of VR-based treatment to improve other types of avoidance, such as agoraphobic avoidance in patients with psychosis [43] or panic disorder with agoraphobia [53], cognitive avoidance in city violence crime victims with PTSD or acute stress disorder [40], alcohol-approach avoidance in patients with substance-use disorder [48], and food avoidance in a patient with bulimia nervosa [57] (see Table S1 for additional details of each study).…”
Section: Avoidancementioning
confidence: 99%
“…Virtual technology may also contribute to the prognostication of future beverage choices (alcoholic vs. non-alcoholic) [70]. There are also reports that VR-CET-based training may lead to changing approach bias via visual and auditory stimuli, thus reducing automatic action tendencies toward alcohol [26]. Elsewhere, a similar task was reported to be a useful and accurate measure of craving in social drinkers, mostly due to its ability to provide realistic scenarios and the sense of immersion in virtual environments [71].…”
Section: Effectiveness Of Exposure To Virtual Reality Environmentsmentioning
confidence: 99%
“…The majority of the available evidence demonstrates the virtual environment's great capacity to induce cravings, amongst others, for alcohol [14], cocaine [15], or nicotine [16][17][18]. Therefore, there are reports of VR applications in the treatment of a range of addictive disorders, including nicotine and alcohol dependence, gambling, or Internet gaming disorders [7,19], with interventions based on cue exposure for smoking [20][21][22] and methamphetamine addiction [23][24][25], or approach and avoidance training for alcohol dependence [6,26]. Nevertheless, studies to date concerning the most widely researched nicotine dependence seem to yield somewhat conflicting results, suggesting a comparable effect of virtual reality cue exposure therapy (VR-CET) to conventional cognitive-behavioral therapy (CBT) interventions [27], greater efficaciousness of CBT-adjuvant VR-CET [20], or no increase in efficacy in response to add-on VR-CET protocol combined with an elevated relapse risk elsewhere [22].…”
Section: Introductionmentioning
confidence: 99%